Estrategias metodológicas para el desarrollo del esquema corporal y la creatividad en los niños y niñas de primer grado de educación básica de la escuela general Manuel Serrano del cantón El Guabo periodo 2014 – 2015. - Dumas Tituana, María Lorena (2014)
This research is based on the methodological strategies for the development of body image and creativity in children of first grade of basic education. The aim of the research is to determine the importance of applying the methodological strategies for the development of body image and creativity in the teaching-learning process in children today brings quality education to the development of students. The results of the investigation it was found that many teachers do not use appropriate for the development of body image and creativity methodological strategies due to lack of training activities to help the knowledge of his body, while the use of games , songs, allow students in school years possess creative skills and enjoy exploring your body actively. WORKSHOP STRUCTURED ACTIVITIES AIMED AT SCHOOL TEACHERS IN FIRST YEAR OF BASIC EDUCATION SCHOOL GENERAL MANUEL SERRANO THE Guabo Canton, SCHEME TO DEVELOP THE BODY AND CREATIVITY: So, to counteract the above problem an alternative proposal entitled raised BODY SCHEME AND CREATIVITY which has been raised in order to inform teachers and parents value with participatory games on the development of laterality and body position in space.